Synthesis of Silver Nanoparticles Dispersed in Various Aqueous Media Using Laser Ablation - M. Tajdidzadeh; B. Z. Azmi; W. Mahmood M. Yunus; Z. Abidin Talib; A. R. Sadrolhosseini; K. Karimzadeh; S. A. Gene; M. Dorraj (The Scientific World Journal)
The particle size, morphology, and stability of Ag-NPs were investigated in the present study. A Q-Switched Nd: YAG pulsed laser (λ = 532 nm, 360 mJ/pulse) was used for ablation of a pure Ag plate for 30 min to prepare Ag-NPs in the organic compound such as ethylene glycol (EG) and biopolymer such as chitosan. The media (EG, chitosan) permitted the making of NPs with well dispersed and average size of Ag-NPs in EG is about 22 nm and in chitosan is about 10 nm in spherical form. Particle size, morphology, and stability of NPs were compared with distilled water as a reference. The stability of the samples was studied by measuring UV-visible absorption spectra of samples after one month. The result indicated that the formation efficiency of NPs in chitosan was higher than other media and NPs in chitosan solution were more stable than other media during one month storage. This method for synthesis of silver NPs could be as a green method due to its environmentally friendly nature.